Macrophages and the Pathogenesis of COPD - Tetley, Teresa D. (Chest, 2002)
Macrophages are long-lived effector cells within the lung. They are reactive, responding to endogenous and exogenous stimuli, as well as proactive, producing mediators that modulate the behavior of surrounding cells. In addition, they play a critical role in the clearance of apoptotic neutrophils. Their role in COPD probably reflects a number of functional properties. However, if the link between increased proteinase burden and tissue destruction and injury in patients with COPD is correct, then macrophages must be very significant. Even though other cells, including epithelial cells and fibroblasts, have been shown to express higher matrix metalloproteinase (MMP) levels in lung tissue from subjects with COPD and emphysema, the numbers of resident cells do not appear to increase by the same factor as that of sequestered macrophages. The combination of a 5- to 10-fold increase in macrophage numbers, the up-regulation of MMPs, and their corelease with other classes of stored proteinases must be highly significant in terms of an increase in proteinase potential in the small airways and respiratory units. This may account for increased tissue destruction and inflammatory mediator activation leading to the pathology that occurs during COPD. Since only about 15% of smokers develop clinically significant disease, it seems likely, in smokers without COPD, that these processes either are strictly controlled or that lung repair mechanisms are more effective.